Diabetic ketoacidosis treatment outcomes and its associated factors among adult patients with diabetes mellitus admitted to public hospitals in Nekemte Town, Ethiopia: a cross-sectional study - Mitiku Yigazu, Daniel; Lema, Matiyos; Bekele, Firomsa; Tesfaye Daka, Dawit; Samuel, Dagim; Addisu, Nigatu (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundDiabetic ketoacidosis (DKA) is a serious and acute complication of diabetes mellitus. In Ethiopia, the mortality associated with acute diabetes complications ranges from 9.8% to 12%. Despite this, there is limited information on the clinical outcomes of DKA in our study location. Therefore, this study aimed to assess the magnitude and associated factors of DKA treatment outcomes among adult patients with diabetes admitted to public hospitals in Nekemte Town, Ethiopia.ObjectiveTo assess the DKA treatment outcomes and their associated factors among adult patients with diabetes admitted to public hospitals in Nekemte Town.MethodsA 5-year cross-sectional study was conducted using a systematic random sampling technique among 201 patients from 1 July to 31 August 2023. DKA treatment outcomes were assessed at discharge. Pharmacists collected data by reviewing patient charts using Kobo Toolbox software. The data were then exported to SPSS Version 27 for analysis. Both bivariable and multivariable logistic regression analyses were performed. Variables with a P-value < 0.25 in the bivariable logistic regression were entered into the multivariable regression analysis to control for potential confounders. An adjusted odds ratio with a 95% confidence interval was used to identify predictors of treatment outcomes. A P-value < 0.05 was considered significant in the multivariable analysis.ResultComplete data was available for 201 patients admitted with DKA. The majority, 178 (88.6%), improved and were discharged. Independent predictors of DKA recovery were comorbidities [AOR: 3.45, 95% CI: 1.33, 9.72], admission Glasgow Coma Scale (GCS) score (<8) [AOR: 2.74, 95% CI: 1.02, 7.34], random blood glucose (RBS) (≥ 500) [AOR: 3.07 (95% CI: 1.12, 8.39)], and urine ketones (≥ +3) [AOR: 3.24, 95% CI: 1.18, 8.88].Conclusion and recommendationMost of the treated patients with DKA were discharged with improvement. Comorbidity, admission GCS, RBS, and urine ketones were independently associated with DKA recovery. In general, significant consideration should be given to DKA prevention, early detection, and appropriate hospital management.